PENGARUH KONTEN PRODUK, ENDORSEMENTS, DAN LIVE STREAMING TERHADAP MINAT BELI KONSUMEN VIA E-COMMERCE - Haaniyah, Warda; Abadiyah, Rifdah; Andriani, Dewi (Buletin Studi Ekonomi; VOLUME.28.NO.02.TAHUN.2023, 2025)
The purpose of this study is to understand the influence of product content, endorsements, and live streaming on consumer trust in e-commerce managed by UD Ivan Collection. This study adopts a quantitative approach using the convenience sampling method to identify respondents who have purchased products at UD Ivan Collection. In this study, the sample size used ranged from 30 to 300 respondents, which was designed to represent the research findings. The data used in this study consisted of secondary data obtained from journals or books, as well as primary data collected through surveys and questionnaires. The data analysis technique applied in this study was using SPSS version 27. The analysis in this observation includes instrument testing (validity and reliability), model testing (classical assumptions), and hypothesis testing (multiple regression, t-test, F-test, and R2) to ensure instrument reliability, model validity, and the contribution of independent variables to the dependent variable.